Pelaksanaan Sita Jaminan terhadap Nasabah Wanprestasi di PT. Bank Pembiayaan Rakyat Syariah (BPRS) Sukowati Sragen - Saputra, Dimas Angga Prabu; Mayasari, Hanita (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract The purpose of this study was to determine the implementation of collateral confiscation against defaulting customers at PT BPRS Sukowati Sragen. The type of research used in this thesis is empirical legal research. The data used are primary data and secondary data. Primary data obtained through interviews while secondary data consisting of primary, secondary and tertiary legal materials. Data collection using interviews and literature studies. The implementation of collateral confiscation against defaulting customers at PT BPRS Sukowati Sragen is to provide leeway to debtors or customers to be able to make payments within a certain time limit. If the customer still does not make payments then the settlement is by deliberation and consensus, namely sending a Warning Letter. three times, Broadly speaking, the provision of Warning Letters is carried out sequentially where the type of Warning Letter I is valid after 1 (one) month after maturity. If in Warning Letter I, the customer does not have the intention to pay off the arrears, it will be upgraded to Warning Letter II until the provision of Warning Letter III. If the warning letter also does not get any response from the debtor or defaulting customer, PT BPRS Sukowati Sragen then submits a request for collateral confiscation to the National Sharia Arbitration Board. After the National Sharia Arbitration Board's decision regarding the confiscation of collateral is issued. Then the PT BPRS Sukowati Sragen submits an application for bail confiscation to the authorized Religious Court where the object of the bail confiscation is located. Keywords: Legal Review, Collateral Confiscation, Default. Abstrak Tujuan penelitian ini adalah untuk mengetahui pelaksanaan sita jaminan terhadap nasabah wanprestasi di PT. BPRS Sukowati Sragen. Jenis penelitian yang digunakan dalam skripsi ini adalah penelitian hukum empiris. Data yang digunakan berupa data primer dan data sekunder. Data primer diperoleh melalui wawancara sedangkan data sekunder yang terdiri dari bahan hukum primer, sekunder dan tersier. Pengumpulan data menggunakan wawancara dan studi kepustakaan. Pelaksanaan sita jaminan terhadap nasabah wanprestasi di PT. BPRS Sukowati Sragen adalah memberikan kelonggaran waktu kepada debitur atau nasabah untuk dapat melakukan pembayaran sampai batas waktu tertentu. Jika nasabah tetap tidak melakukan pembayaran maka penyelesaian secara musyawarah dan mufakat, yaitu mengirimkan Surat Peringatan. sebanyak tiga kali, Secara garis besar, pemberian Surat Peringatan dilakukan berurutan dimana jenis Surat Peringatan I berlaku setelah 1 (satu) bulan setelah jatuh tempo. Jika dalam Surat Peringatan I, nasabah tidak mempunyai itikad dalam melunasi tunggakan maka akan ditingkatkan ke Surat Peringatan II sampai kepada pemberian Surat Peringatan III. Jika surat peringatan juga tidak mendapatkan tanggapan sama sekali dari debitur atau nasabah wanprestasi maka selanjutnya pihak PT. BPRS Sukowati Sragen mengajukan permohonan sita jaminan kepada Badan Arbitrase Syariah Nasional. Setelah keluar putusan Badan Arbitrase Syariah Nasional mengenai sita jaminan. Kemudian pihak PT. BPRS Sukowati Sragen mengajukan permohonan sita jaminan kepada Pengadilan Agama yang berwenang dimana obyek sita jaminan tersebut berada. Kata Kunci: Tinjauan Hukum, Sita Jaminan, Wanprestasi.